Myocardial infarction, due to blunt chest trauma - Jesús E. Fonseca Iragorri; Luis Armando Caicedo R (Colombia Medica, 1981)
A 32-year-old male, without previous history of ischemic heart disease or angiographic evidence of coronary arteriosclerosis, presented after a blunt chest trauma, an acute anteroseptal wall myocardial infarction due to occlusion of the left anterior descending coronary artery. Collateral circulation from the right coronary artery filling the affected vessel was visualized by angiography four and a half months after the accident. Special discussion is given to similar documented cases reported in the literature, and some considerations on treatment of this type of patients are made.